Extended charge-transfer model for NaxCo[Fe(CN)6]0.82. (29th March 2021) - Moritomo, Yutaka; Tachihara, Hiroki; Iwaizumi, Hiroki; Shibata, Takayuki; Niwa, Hideharu
Abstract: Cobalt Prussian blue analogues (Na x Co[Fe(CN)6 ] y ; x ∼ 4 y − 3 ) whose valences are close to Co 3 + and Fe 2 + show characteristic phase transitions triggered by cooperative charge transfer (CT) from Fe 2 + to Co 3 + . Here, we extended the cooperative CT to the entire region of sodium concentration ( 0 ≤ x ≤ 4 y − 2 ). We systematically investigated (1) upper ( T c u ) and lower ( T c l ) critical temperature, (2) variation of the [ Fe 2 + (CN)6 ] 4 − ([ Fe 3 + (CN)6 ] 3 − ) concentration, and (3) spectral weight ( I ET ) due to electron transfer from Fe 2 + to Co 3 + of thin films of Na x Co[Fe(CN)6 ]0.82 against x . In a wide x region from 0.00 to 0.57, we observed first-order phase transition triggered by the cooperative CT. The extended CT model reproduces the x -dependent behavior of the [Fe II (CN)6 ] 4 − ([Fe III (CN)6 ] 3 − ) concentration and I ET, except for the high- x region above x ∼ 0.9 .